Prognostic and Predictive Significance of Microsatellite Status in Patients with Colorectal Cancer in Stage II and Stage III Disease: Single-Centre Experience - Perović, Jelena; Radić, Jelena; Djuric, Aleksandar; Marjanovic, Marko; Urosevic, Teodora; Radovanović, Bojan; Kožik, Bojana (Archive of Oncology, 2025)
Background: Colorectal cancer (CRC) is one of the leading causes of cancer-related morbidity and mortality worldwide. Microsatellite instability (MSI) is a crucial biomarker with prognostic and predictive value, influencing treatment decisions in CRC. Methods: This retrospective study investigated the impact of the MSI status on clinical outcomes in 184 CRC patients treated at the Oncology Institute of Vojvodina between 2018 and 2023. The MSI status was determined using the immunohistochemical analysis of mismatch repair proteins.Results: Among the cohort, 75% of tumors were microsatellite-stable (MSS), 4.3% exhibited low MSI (MSI-L), and 20.6% displayed high MSI (MSI-H). MSI-H tumors were significantly associated with right-sided CRC, mucinous differentiation, and female gender (p
Keywords: Colorectal Cancer; Microsatellite Instability; Adjuvant Chemotherapy; Stage II; Stage III